Roma kivándorlás - Bíró, Liza M. (Hungary : MTV - Hungarian Television, 2005)
A short film about the Roma in Slovakia who, like many of their fellow citizens, set out to find work in Western European or overseas countries. In many cases the authorities refused entry to Czech and Slovakian Roma migrants already at the airport. Due to the rather high Roma exodus, temporary visa obligation was also restored in several Western European countries. The film attempts to follow and decipher the logics of migration from both sides.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films